2019
DOI: 10.1111/jocn.14777
|View full text |Cite
|
Sign up to set email alerts
|

Do family health conversations impact patients with glioblastoma multiforme and their family members?

Abstract: Aims and objectives To assess the impact of family health conversations (FamHC) as a supplement to conventional care on health‐related quality of life (HRQoL), family functioning (FFSS) and family hardiness or resilience (FHI) 4 and 14 weeks postoperatively among patients with glioblastoma multiforme and their family members. Background There is a lack of knowledge about the efficiency of FamHC among families experiencing glioblastoma multiforme. Design A quasi‐experimental pre‐ and post‐test design adhering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…The existing evidence suggests that conversations based on Family Systems Nursing can improve families' perceptions of the support they receive from professional caregivers (Petursdottir & Svavarsdottir, 2019;Sveinbjarnardottir et al, 2013) and may also improve family functioning (Lee et al, 2018;Sundin et al, 2016) and possibly health-related quality of life (Lämås et al, 2016) and caregiver burden (Petursdottir & Svavarsdottir, 2019). Results are, however, somewhat inconsistent with respect to these outcomes (Dorell et al, 2017;Faarup et al, 2019;Østergaard et al, 2018). In addition, the effects of these conversations in HHC have not yet been studied in an experimental design, with the exception of palliative home care (Petursdottir & Svavarsdottir, 2019)…”
Section: Since Then Most Experiments and Quasi-experiments On Familymentioning
confidence: 99%
“…The existing evidence suggests that conversations based on Family Systems Nursing can improve families' perceptions of the support they receive from professional caregivers (Petursdottir & Svavarsdottir, 2019;Sveinbjarnardottir et al, 2013) and may also improve family functioning (Lee et al, 2018;Sundin et al, 2016) and possibly health-related quality of life (Lämås et al, 2016) and caregiver burden (Petursdottir & Svavarsdottir, 2019). Results are, however, somewhat inconsistent with respect to these outcomes (Dorell et al, 2017;Faarup et al, 2019;Østergaard et al, 2018). In addition, the effects of these conversations in HHC have not yet been studied in an experimental design, with the exception of palliative home care (Petursdottir & Svavarsdottir, 2019)…”
Section: Since Then Most Experiments and Quasi-experiments On Familymentioning
confidence: 99%
“…Table 2 outlines the main characteristics of the studies. In terms of study design, 13 studies were randomized controlled trial (RCT) design (Badger et al, 2013, 2020; Belgacem et al, 2013; Couper et al, 2015; Hendrix et al, 2011; Kochaki Nejad et al, 2016; Lewis et al, 2019; McCaughan et al, 2018; Moghaddam Tabrizi & Alizadeh, 2018; Northouse et al, 2013; Sherwood et al, 2012; Thakur et al, 2019; Valeberg et al, 2013), whereas the remaining 6 studies were quasi-experimental studies design (Badger et al, 2011; Bilgin & Gozum, 2016; Çol & Kılıç, 2019; Faarup et al, 2019; Li et al, 2015; Titler et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies identified the target population as couples in which one of the partners had been diagnosed with cancer and the spouse was the primary caregiver (Çol & Kılıç, 2019; Couper et al, 2015; Lewis et al, 2019; Li et al, 2015; McCaughan et al, 2018). In the remaining studies, the patient was asked to identify the family caregiver most involved in their care or his or her primary source of emotional and/or physical support, but this person was not necessarily their partner (Badger et al, 2011, 2013, 2020; Belgacem et al, 2013; Bilgin & Gozum, 2016; Faarup et al, 2019; Hendrix et al, 2011; Moghaddam Tabrizi & Alizadeh, 2018; Northouse et al, 2013; Sherwood et al, 2012; Titler et al, 2017; Valeberg et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Family interventions do not seem to have any effect on health‐related quality of life, self‐care manners and signs of depression. (Agren et al, 2012; Faarup et al, 2019; Østergaard, Mahrer‐Imhof, et al, 2018; Schwarz et al, 2008); however, social support from spouses, significant others, family and friends play an essential part in supporting with numerous of self‐care‐related behaviours in patients with heart failure (Graven & Grant, 2014; Stromberg, 2013).…”
Section: Introductionmentioning
confidence: 99%